Grit as a Mediator of the Relationship Between Stress, Social Support, and Subjective Well-Being among First-year Indonesian Muslim Students from Out of Town - Rachmahana, Ratna Syifa'a; Damri, Rafi; Hutagalung, Fonny Dameaty (International Journal of Islamic Educational Psychology, 2025)
Students living away from home often face challenges that diminish their well-being. This study examine stress as a risk factor and social support as a protective factor for subjective well-being. The relationship between social support and stress on the subjective well-being of students living away from home can be facilitated by other variables, one of which is grit. This study examined how grit acts as a mediator in the relationship between social support and stress, influencing the subjective well-being of students living away from home. This study employed a non-random, purposive sampling technique, which enabled the successful analysis of 262 data points. The analysis included tests of normality and multicollinearity assumptions, as well as mediation hypothesis testing with 5,000 bootstrapping resamples. Results showed that subjective well-being is positively correlated with social support and grit, and negatively correlated with stress. Furthermore, grit can mediate the influence of social support and stress on subjective well-being. These results have important implications for students' stress management and interpersonal relationship maintenance. Institutions can support student well-being by creating collaborative learning environments. Recommendations for further research are offered, including increasing sample size, involving more diverse demographics, and incorporating other psychological variables to clarify and increase the complexity of this model. In addition, Islamic-based research can integrate models with Islamic psychological variables, such as istiqamah and sa'adah.